Exploration and Research on the Propagation Law of Seepage Risk Network in Tailings Storage Facility. (8th November 2021) - Zhen, Zhixin; Ma, Xuewei; Ma, Bo
Abstract : The seepage accident of a tailings pond poses a serious threat to the stability of tailings dams and the surrounding environment. To reduce the occurrence of seepage accidents, this paper studies the identification of seepage hazards, the propagation law of seepage risk, the importance of hazards, and the priority of hazard treatment. To overcome the subjectivity and omission of hazard identification, according to the complexity and dynamics of tailings seepage, this paper proposes the evidence-based identification method of three-dimensional seepage hazards (EIMTSH) to identify the hazards of the tailings seepage system and the relationship between hazards. Then, on the basis of identifying the hazards of the tailings seepage system, the propagation network of seepage risk in tailing ponds (PNSRTP) is constructed based on the complex network theory. By analyzing the characteristics of the PNSRTP, it can be found that the propagation of seepage risk is scale-free and small-world. Through the node deletion method, this paper finds that the nodes with a higher degree value can reduce the network efficiency more quickly and should be governed first. By giving priority to the treatment of hazards with higher degree, the propagation of seepage risk can be reduced more quickly and the risk management level of tailings ponds can be improved, which is helpful to realize the sustainable development of mining production.